1986
DOI: 10.3109/10641968609045483
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Hypertension : Aetiology and Outcome in 83 Patients

Abstract: To evaluate the current pattern of aetiology and outcome in malignant hypertension, we reviewed all medical records of patients presenting between 1979 and 1985 who fulfilled WHO criteria for malignant hypertension. There were 83 patients, 43 males (52%) and 40 females (48%). Primary malignant hypertension was diagnosed in 17 cases (20%) and secondary lesions in 66 cases (80%). Overall one year survival was 94%, and 5 year survival 75%, which is similar to recent reports. Initial serum creatinine was a prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…22,23 smoking has not been found to be an important factor in our study. This is in keeping with the generally low levels of smoking reported in Nigerians.…”
Section: Discussionmentioning
confidence: 38%
“…22,23 smoking has not been found to be an important factor in our study. This is in keeping with the generally low levels of smoking reported in Nigerians.…”
Section: Discussionmentioning
confidence: 38%
“…1 Safe and effective antihypertensive drugs were first developed in the 1960s and were shown to dramatically improve the prognosis associated with malignant hypertension. 2,3 Over the next few decades, the widespread use of an expanding armamentarium of blood pressure-lowering drugs to patients at risk of malignant hypertension effectively eradicated this condition from most developed countries. Subsequently, the provision of blood pressure-lowering treatments to a much broader group of patients at risk of serious cardiovascular diseases, such as stroke and coronary heart disease, among whom blood pressure levels were often only modestly elevated, contributed importantly to the declines in stroke and coronary disease deaths rates experienced by most Western populations.…”
mentioning
confidence: 99%
“…[10,11] IgAN is the most common form of primary glomerulonephritis among patients undergoing renal biopsy and is also one of the major causes of secondary malignant hypertension and ESRD. [20][21][22][23][24] In patients with IgAN-MHT, we previously found that the ischemic lesions and the glomerular background lesions both contributed to the impairment of renal function at presentation. [11] In the literature, it was reported that the genetic variants in the chromogranin A promoter were not only associated with hypertension, but also with hypertensive ESRD in primary hypertension [7,8] ; therefore, whether CHGA gene genetic variants affect onset of malignant hypertension and target-organ damage in secondary MTH raised special interest.…”
Section: Discussionmentioning
confidence: 99%